Analisis Postur Tubuh Operator pada Saat Bekerja Menggunakan Metode Ovako Working Analysis System (OWAS) - Firman Zuhuri Yanto; Sutrisno Sutrisno (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
One of the interesting topics that is needed to be analyzed and studied more deeply in a study is analysis to find out the posture of a worker in carrying out a job. Work posture is a decisive point in analyzing the effectiveness of a job. If operators have a good and ergonomic work posture, they certainly have good job results. Operators who easily experience fatigue can be seen from the results of their completed work. Their work decreases and is not as expected, followed by various musculoskeletal complaints on parts of the skeletal muscles suffered by a person ranging from very slight to severe complaints. The complaints to injury are usually termed complaints of musculoskeletal disorders (MSDs) or complaints of musculoskeletal injuries. The OWAS method is a method that provides output in the form of a category of work attitudes that are at risk of work accidents in the musculoskeletal section. Based on the results of research using the OWAS method, it is known that out of the 7 operators observed, 3 operators are in category 2, namely dangerous or require improvement in work posture, while 4 operators are in safe category